Thermoregulatory responses to combined moderate heat stress and hypoxia. (October 2016) - Low, David A.; Bailey, Tom G.; Timothy Cable, Nigel; Jones, Helen
Abstract: Objective: The aim of this study was to examine the cutaneous vascular and sudomotor responses to combined moderate passive heat stress and normobaric hypoxia. Method: Thirteen healthy young males, dressed in a water‐perfused suit, underwent passive heating (Δcore temperature ~0.7°C) twice (Normoxia; 20.9% O2 and Hypoxia; 13% O2 ). Chest and forearm skin blood flow (SkBF; laser‐Doppler flux) and sweat rate (SR; capacitance hygrometry), core (intestinal pill), and skin temperatures, were recorded. Results: Hypoxia reduced baseline oxygen saturation (98±1 vs 89±6%, P <.001) and elevated chest ( P =.03) and forearm SkBF ( P =.03), and HR (64±9 vs 69±8 beats.min −1, P <.01). During heating, mean body temperature ( T ¯ BODY ) thresholds for SkBF ( P =.41) and SR ( P =.28) elevations were not different between trials. The SkBF: T ¯ BODY linear sensitivity during the initial phase of heating was lower at the chest ( P =.035) but not different at the forearm ( P =.17) during hypoxia. With increasing levels of heating chest SkBF was not different ( P =.55) but forearm SkBF was lower ( P <.01) during hypoxia. Chest ( P =.85) and forearm ( P =.79) SR: T ¯ BODY linear sensitivities were not different between trials. Conclusion: While sudomotor responses and the initiation of cutaneous blood flow elevations are unaffected, hypoxia differentially effects regional SkBF responses during moderate passive heating.